Haemodynamic characteristics of middle uterine artery in crossbred cows with uterine torsion - RAJA, S; SATHESHKUMAR, S; SELVARAJU, M; PRABAHARAN, V; RAMACHANDRAN, M; PARAMASIVAM, A (The Indian Journal of Animal Sciences, 2024)
The aim of the present study was to evaluate the haemodynamics of uterine blood flow in uterine torsion and record the period of resumption of ovarian cyclicity in cattle with uterine torsion. Crossbred cows with term gestation and straining for parturition due to post-cervical uterine torsion were selected for the study. Transrectal ultrasonographic assessment for measuring the doppler indices of middle uterine artery for both ipsilateral and contralateral side before and after detorsion was studied. Haemodynamic parameters such as blood flow volume (BFV), time-averaged peak velocity (TAP), resistance index (RI) and pulsatility index (PI) were assessed by using minimum three cardiac cycles. Blood samples were collected for haematological and biochemical assessment. Before detorsion, the PI value was high in ipsilateral side of uterine torsion and significant decrease could be observed after detorsion. However, BFV significantly increased after detorsion in both ipsilateral and contralateral side of uterine torsion when compared to the pre-detorsion values. Haematological and serum biochemical values were within the reference values and no significant observation could be made out of this in torsion affected cows. Two out of six animals (33.33%) exhibited the heat signs within three months of calving. In conclusion the blood flow volume was evidently increased after detorsion; however, the viability of the fetus was decided by the occurrence, duration and degree of uterine torsion.